Consumer acceptance of provitamin A orange maize in rural Zambia - Meenakshi, Jonnalagadda V.; Manyong, Victor M.; Tomlins, Keith; Hamukwala, Priscilla; Zulu, Rodah; Mungoma, Catherine; Banerji, Abhijit (International Food Policy Research Institute, 2010)
This study analyzes consumer acceptance of biofortified orange maize in rural Zambia by eliciting consumers' willingness to pay. It attempts to examine the impact of nutrition information, comparing the use of simulated radio versus community leaders in transmitting the nutrition message, on consumer acceptance. Finally, it assesses whether product experience in a home-use setting influences the magnitude of premiums or discounts.